2006
DOI: 10.1038/sj.eye.6702498
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous humour levels of cytokines are correlated to vitreous levels and severity of macular oedema in branch retinal vein occlusion

Abstract: Aim To investigate whether the aqueous levels of vascular endothelial growth factor (VEGF) and interleukin-6 (IL-6) are correlated to the vitreous levels of these substances and to the severity of macular oedema in branch retinal vein occlusion (BRVO). Methods Aqueous and vitreous samples were obtained during cataract and vitreous surgery from 24 patients (24 eyes) with macular oedema in BRVO. The VEGF and IL-6 levels in aqueous humour, vitreous fluid, and plasma were determined by enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
181
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(194 citation statements)
references
References 40 publications
6
181
2
5
Order By: Relevance
“…In this regard, the authors may have overlooked important factors for the production of EPO, such as nephropathy status, Hb levels, and coexisting vascular disease. 3 The authors have shown ingenuity in their study; however, we reckon that it would have been better served with a comprehensive outlook of the risk factors being studied. We appreciate the comments of Dr Uparkar regarding our article.…”
Section: Eyementioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the authors may have overlooked important factors for the production of EPO, such as nephropathy status, Hb levels, and coexisting vascular disease. 3 The authors have shown ingenuity in their study; however, we reckon that it would have been better served with a comprehensive outlook of the risk factors being studied. We appreciate the comments of Dr Uparkar regarding our article.…”
Section: Eyementioning
confidence: 99%
“…2 Earlier reports show that the correction of anaemia (and also supplementation of EPO) decrease the effects of retinopathy with structural improvement, possibly through the improved oxygenation of the macula. 2,3 It would be fallacious then to compare the acute imbalance of retinal vein occlusion (RVO) cases, with DME. Also, EPO level in the DME group was found to be 430 mU/ml (41-3000), and in the RVO group, it was 91.3 mU/ml (30-417).…”
Section: Eyementioning
confidence: 99%
See 1 more Smart Citation
“…В настоя-щее время определено, что больные с ОВС характе-ризуются повышенным уровнем ВЭФР, при этом степень тяжести макулярного отека прямо коррели-рует с уровнем ВЭФР и ИЛ-6 [2,20]. Были выявле-ны также аналогичные взаимосвязи между уровнем ВЭФР, неоваскуляризацией радужки и сосудистой проницаемостью у пациентов с ишемической ОВС [21].…”
unclassified
“…8,9 Particularly, the marked rise of VEGF levels in BRVO patients has been studied intensively. 10,11 Historically, observation, lasercoagulation or surgical treatments (radial optic neurotomy, retinochoroidal anastomosis, arteriovenous (AV) sheatotomy) represented the only available therapeutic options.…”
mentioning
confidence: 99%